167 Clinicians' perspectives on morphine use in chronic breathlessness: Findings from an implementation survey. (14th March 2023) - Mohamed, Ahmed; Pearson, Mark; Date, Kathryn; Williams, Bronwen; Bajwah, Sabrina; Johnson, Miriam; Fallon, Marie
Abstract : Background: Morphine may help people with chronic breathlessness. This sub-study investigates clinicians' perspectives on morphine use as part of the Morphine And BrEathLessness (MABEL) trial to assess the effectiveness and cost-effectiveness of morphine in chronic breathlessness. Method: Mixed-methods study using Normalisation Process Theory to organise data collection and analysis of clinicians' perspectives on morphine use for chronic breathlessness. Clinicians completed two surveys: 1.Learning Needs Assessment (LNA) survey; 2.Modified Normalisation Measurement instrument (NoMAD) at two time-points (immediately and four months post-training) to identify implementation barriers and facilitators. Results: 59 clinicians were recruited from 12 sites, (28 doctors; 22 non-prescriber nurses; 6 prescriber nurses; 3 other healthcare professionals; 90% hospital-based; 74% female; years of experience 1 to >15 years). 1.LNA survey. More than two-thirds of clinicians strongly agreed, agreed, or somewhat agreed they had learning needs about using morphine for chronic breathlessness. 2.NoMAD 1. 93% saw the potential value of morphine for breathlessness and drive appropriate use of it. However, only one third agreed that sufficient staff training and resources were available to support use of morphine for breathlessness in practice. NoMAD 2 showed a small increase in the proportion agreeing that the intervention was familiar and felt 'normal' compared to NoMAD 1 (70% to 85%). Conclusion: Clinicians recognise learning needs about the safe prescription and management of morphine for chronic breathlessness in practice. The potential value of morphine is recognised, but lack of training and resources are barriers to implementation. Funding: National Institute for Health Research HTA 17/34/01.